2011
DOI: 10.1007/s12264-011-1034-4
|View full text |Cite
|
Sign up to set email alerts
|

Noradrenaline regulates substance P release from rat dorsal root ganglion neurons in vitro

Abstract: NA may significantly increase CAP-evoked SP release through activation of α-adrenoreceptors, which may contribute to noradrenergic pain modulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…The α-adrenoceptors include α 1A , α 1B , α 1D , α 2A , α 2B , and α 2C subtypes, and β-adrenoceptors into β 1 , β 2 , and β 3 subtypes [ 21 ]. They have been reported to be expressed in primary sensory neurons with their cell bodies located in the dorsal root ganglia (DRGs) [ 22 , 23 ]. Previous studies have suggested that the β 1 and β 2 subtypes are involved in the adrenergic activation [ 24 ] that may play a role in colonic transit.…”
Section: Introductionmentioning
confidence: 99%
“…The α-adrenoceptors include α 1A , α 1B , α 1D , α 2A , α 2B , and α 2C subtypes, and β-adrenoceptors into β 1 , β 2 , and β 3 subtypes [ 21 ]. They have been reported to be expressed in primary sensory neurons with their cell bodies located in the dorsal root ganglia (DRGs) [ 22 , 23 ]. Previous studies have suggested that the β 1 and β 2 subtypes are involved in the adrenergic activation [ 24 ] that may play a role in colonic transit.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, a positive loop between NA and SP has been previously described, in which NA promotes SP release by binding to α-adrenoceptor. 50 , 52 , 53 In this vein, it is reasonable to hypothesize that despite blocking the β-receptors located on inflammatory cells, NA can still favor SP release through α-adrenoceptor. Therefore, blocking NK1R would inhibit the inflammatory response by preventing SP effects on both the afferent and efferent pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Recordings from the dorsal root attached to an excised DRG preparation taken from rats with chronic constriction injury of the sciatic nerve revealed that C, Aδ, and Aβ neurons responded to NE and to an α 2 receptor agonist applied topically to the DRG (Zhang et al, 1997). NE activation of α receptors in peptidergic nociceptors has also been reported to enhance the release of substance P (Wang et al, 2011c). Note that these studies rarely distinguished direct effects of NE from indirect effects mediated by other cell types in the ganglion or possibly even in the culture dish.…”
Section: Interactions Among Sympathetic Activity Innate Immune Fumentioning
confidence: 99%